Acute haemolytic anaemia and myolysis due to G6PD deficiency - Mangat, Chetna (BMJ Publishing Group, 2014)
A 2-year-old African-American male patient with sickle cell trait developed cough, red coloured urine, pallor and fatigue. The patient was hospitalised. Diagnostic workup showed that he was glucose 6 phosphate dehydrogenase (G6PD) deficient in erythrocytes. He also had chest X-ray findings of pneumonia. His urine examination showed the presence of haemoglobin and myoglobin. On repeated questioning it was found that he had a moth ball in his mouth a few days prior to this medical episode. This case illustrates a rarely described complication of myolysis in G6PD deficient persons on exposure to a strong oxidant. A review of the literature showed that most people with G6PD deficiency tolerate exercise well without untoward effect in muscles. However, assay of myoglobin in urine has not been routinely performed in these patients during acute haemolytic episode, and thus it is uncertain how frequent myoglobulinaemia occurs in a similar stress situation.